1999
DOI: 10.1111/j.1574-695x.1999.tb01335.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time post mortem on the concentration of endotoxin in rat organs: implications for sudden infant death syndrome (SIDS)

Abstract: The aim of the study was to test the following hypotheses: (i) that endotoxin injected 40 min prior to death can be detected in rat organs post mortem and (ii) that endotoxin levels do not change with increasing time post mortem. Rats were injected with or without endotoxin in buffered saline, 40 min prior to being killed. Endotoxin levels in rat organs were assessed using a Limulus amoebocyte assay. The effect of storage time post mortem was assessed by following various storage regimes at 25 degrees C and 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, this also seems unlikely as bacteria are not routinely cultured from the blood of SIDS victims and the rapid temperature drop post‐mortem as the body is chilled does not favour microbial growth. In addition, experiments in which rats were injected ante‐mortem with endotoxin have also shown that there are only small changes in toxin levels after death and subsequent storage [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, this also seems unlikely as bacteria are not routinely cultured from the blood of SIDS victims and the rapid temperature drop post‐mortem as the body is chilled does not favour microbial growth. In addition, experiments in which rats were injected ante‐mortem with endotoxin have also shown that there are only small changes in toxin levels after death and subsequent storage [10].…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of endotoxin in blood or tissues remains fraught with problems, even during life [13], and there is considerable controversy as to the effect of post‐mortem storage on endotoxin levels; however, in a carefully designed animal model we were able to show that endotoxin levels in blood and a range of organs were higher in rats injected with endotoxin immediately before death compared to control animals and that these results were stable for up to 102 h after death [14]. These results prompted us to study endotoxin levels in blood and tissue samples taken at autopsy from SIDS infants and controls.…”
Section: Introductionmentioning
confidence: 87%
“…New evidence indicates that Staphylococcus aureus and its pyrogenic toxins were identified in over half of SIDS cases [6] and Escherichia coli isolated from extra‐intestinal sites [22]. The criticisms that detection of endotoxin and Gram‐negative bacteria in SIDS cases are overgrowth from the gut are addressed in this issue [22,26].…”
Section: Which Micro‐organisms Are Implicated In Sids?mentioning
confidence: 99%